2022
DOI: 10.1109/jeds.2022.3198138
|View full text |Cite
|
Sign up to set email alerts
|

BEOL Integrated Ferroelectric HfO₂-Based Capacitors for FeRAM: Extrapolation of Reliability Performance to Use Conditions

Abstract: Si doped HfO2 based ferroelectric capacitors integrated into Back-End-Of-Line (BEOL) 130 nm CMOS technology were investigated in regard to critical reliability parameters for their implementation in non-volatile one-transistor one-capacitor ferroelectric random-access memory applications. The assessed reliability parameters are electric field, capacitor area, and temperature and are evaluated on single and parallel structured capacitors to understand their respective impact on wake-up, fatigue, imprint, and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…In addition to the P r , reliability, such as endurance, is also an important parameter for the FeRAM application. In this work, the sample survived until 10 7 cycles under the electric field stress, which is in line with the reported value. , It was recently shown that scaling the capacitor area to more realistic values compared to the large test capacitors used in this study will further increase the endurance …”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…In addition to the P r , reliability, such as endurance, is also an important parameter for the FeRAM application. In this work, the sample survived until 10 7 cycles under the electric field stress, which is in line with the reported value. , It was recently shown that scaling the capacitor area to more realistic values compared to the large test capacitors used in this study will further increase the endurance …”
Section: Resultssupporting
confidence: 89%
“…19,30 It was recently shown that scaling the capacitor area to more realistic values compared to the large test capacitors used in this study will further increase the endurance. 35…”
Section: Resultsmentioning
confidence: 99%
“…However, the FeRAM based on ferroelectric (Hf,Zr)O 2 has been reported to achieve 10 12 level endurance and there have been optimistic predictions on the achievement of even 10 15 endurance. [ 94b,130 ] Moreover, the possibility of sub‐nanosecond polarization switching upon the application of a sufficiently high electric field has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The currently achieved endurance for the FeRAM with a reasonable operation electric field is on the order of 10 12 , and an endurance of 10 15 was recently predicted via extrapolation. [ 130 ] Further, for the FeFET, the maximum achieved endurance is in the order of 10 10 . [ 131 ]…”
Section: Semiconductor Applications Based On Emerging Ferroelectricsmentioning
confidence: 99%
“…Polarization retention at 85 °C is now discussed, considering imprint as the main limiting factor. [25,36] Imprint was analyzed for each of the capacitor stacks and summarized in Figure 7 (for details see Supporting Information). A more substantial initial hysteresis shift leads to a more significant imprint slope in one direction.…”
Section: Top Electrode Comparisonmentioning
confidence: 99%